Expectations, concerns and experiences of rehabilitation patients during the COVID-19 pandemic in Germany: a qualitative analysis of online forum posts - Kübra Altinok; Fabian Erdsiek; Yüce Yilmaz-Aslan; Patrick Brzoska (BMC, 2021)
Abstract Background The COVID-19 pandemic, as well as efforts to prevent its spread, have had a strong impact on the delivery of rehabilitative services in Germany. While several studies have addressed the impact of these developments on health service providers and COVID-19 patients, little is known about its impact on patients in need of rehabilitative treatment because of other conditions. This study aims to identify expectations, concerns and experiences of rehabilitation patients related to service delivery in this situation. Methods Using a qualitative study design, user posts from six German online forums between March and Mid-November 2020 were systematically searched with respect to experiences, concerns and expectations of health care users toward receiving rehabilitative treatment. We used qualitative content analysis with inductive coding as our methodological approach. Results Users fearing physical or psychological impairment were concerned about not receiving timely or effective treatment due to closed hospitals, reduced treatments and limited admissions. In contrast, patients more concerned about getting infected with COVID-19 worried about the effectiveness of protective measures and being denied postponement of treatment by the funding bodies. During their stay, some patients reported feeling isolated due to contact restrictions and did not feel their treatment was effective, while others reported being satisfied and praised hospitals for their efforts to ensure the safety of the patients. Many patients reported communication problems before and during their treatment, including concerns about the safety and effectiveness of their treatment, as well as financial concerns and worries about future treatments. Several users felt that their concerns were disregarded by the hospitals and the funding bodies, leaving them feeling distressed, insecure and dissatisfied. Conclusions While some users report only minor concerns related to the pandemic and its impact on rehabilitation, others report strong concerns relating not only to their own health and safety, but also to financial aspects and their ability to work. Many users feel ignored and disregarded, showing a strong need for more coordinated strategies and improved communication specifically with funding bodies like health insurance companies and the German pension funds.